Ultra-Processed Food Consumption Is Linked to Quality of Life and Mental Distress Among University Students - Ertas Ozturk, Yasemin; Uzdil, Zeynep (Peerj Inc, 2025)
Background Ultra-processed foods (UPFs) are industrial formulations that typically contain little or no whole foods and are often high in added sugars, unhealthy fats, and sodium. Research indicates that higher intake of UPFs correlates with lower overall diet quality, which can exacerbate mental health issues such as anxiety and depression. This study aimed to assess the associations between UPF consumption with health-related quality of life, and mental distress in university students. Method This cross-sectional study consisted of 595 students resident in Samsun/Turkiye. The data were collected face-to-face with a questionnaire. Linear regression analysis was conducted to examine the relationship between the UPFs (% energy), health-related quality of life components and mental distress score (MDS). Receiver operating characteristic (ROC) analysis was conducted to establish the optimal threshold levels regarding physical component summary (PCS12), mental component summary (MCS12) and MDS. Results The UPF ratios were negatively related to PCS12 (beta = -0.112, p = 0.005) and positively associated with MDS (beta = 0.102, p = 0.002) after adjusting for age, sex, physical activity, smoking duration, number of cigarettes and chronic disease. ROC analysis showed that those with UPF consumption above 45.096% had low physical quality of life, those above 50.999% had low mental quality of life, and those above 40.250% had moderate-to-high mental distress. Conclusion Increased consumption of UPFs is associated with a decrease in physical quality of life and an increase in mental distress. Consuming more than 40% from UPFs can lead to mental and physical problems. There is a need for strategies to decrease the intake of UPFs to enhance both physical and mental wellbeing.
Keywords: Mood; Dietary Pattern; Ultra-Processed Foods; Quality of Life; Mental Distress